A Study of the Lima Document in the Christian Unity - MENG, Xiangjiao (Journal of Research for Christianity in China (JRCC), 2024)
The Lima document is a landmark document in the Christian Unity. This article sorts out the history of the production of the Lima document. Meanwhile, this article briefly introduces the theology of the Lima document to present the Lima document’s interpretation of the unity of baptism, eucharist and ministry. The Lima document has provoked a wide range of responses from the world Christian community and deeply influenced ecclesiological studies, liturgical worship and dialogue among the denominations. From the perspective of religious dialogue, the Lima document is the result of the effective development of theological thought through the dialogue of the world Christian community to promote the unity of churches. Rethinking this in the Chinese context, the idea of development is also the essential thought in the dialogue between Chinese culture tradition and Christian culture tradition in the whole system of Chinese culture.